Pengaruh Foot Care Education Terhadap Tingkat Pengetahuan dan Perilaku Perawatan Kaki pada Pasien Diabetes Mellitus Tipe II di Klinik Holistic Nursing Theraphy Probolinggo - Hartono, Dodik; Rahmat, Nafolion Nur (Journal of Nursing Care and Biomoleculer, 2020)
Introduction: Diabetes mellitus is a metabolic disorder disease characterized by hyperglycemia, complications that occur due to DM disease include diabetic foot injuries, even amputations. Foot care education is a way of foot care in DM patients that is useful for preventing diabetic wounds. The aim of the study was to analyzed the effect of educational foot care on knowledge and foot care in patients with type II diabetes mellitus at Clinic Holistic Nursing Therapy Probolinggo. Metho: The research method used pre-experimental by studying the pre-post test of one design group. This research was conducted from 01 to 30 June 2019 at the Clinic Holistic Nursing Theraphy Probolingo. The population is 67 respondents, the sample size is 57 respondents taken by purposive sampling technique. The instrument of this study used a questionnaire sheet, the data were analyzed using paired t-test. Results and Analysis: The results showed that 1) respondents' knowledge before being given less foot care education, and after being given good respondent knowledge. 2) respondent's foot care behavior before being given less foot care education, and after being given good respondent behavior. 3) there is the effect of foot care education on knowledge and foot care in patients with type II diabetes mellitus with a p value of 0,000 <Î± 0,05. Discussion: Foot care education can significantly improve the level of knowledge and foot care in people with type II diabetes mellitus. By being given educator foot care education, diabetes mellitus can increase the level of knowledge and good foot care, so that it can prevent an increase in diabetic ulcers in the foot and also improve the quality of life for patients.